Recent Publications (Quarterly Journal of Economics, 1942)
Recent Publications Get access The Quarterly Journal of Economics, Volume 56, Issue 4, August 1942, Pages 678–683, https://doi.org/10.1093/qje/56.4.678 Published: 01 August 1942